Profiling affective-identity motivation to lead during two years : associations with readiness to lead - Lehtiniemi, Katariina; Kapulainen, Anni (2021)
The aim of this study was to profile the development of affective-identity motivation to lead (AI-MTL) among Finnish highly educated professionals. In addition, differences between these profiles were investigated regarding occupation of leadership positions during the follow-up, leader-supportive organizational climate, and occupational well-being. This study was part of the MOTILEAD-project implemented in the Department of Psychology in University of Jyväskylä and the longitudinal data was collected in 2017 and 2019. Our sample consisted of those professionals who were not leaders at the study baseline (n = 372). During the follow-up, part of them (17%) occupied a leadership position. The results indicated AI-MTL to appear quite stable across two time points as we identified three stable latent profiles: Low-Stable AI- MTL (25%), Moderate-Stable AI-MTL (55%), and High-Stable AI-MTL (20%). Professionals with low AI-MTL were less likely to occupy leadership positions during the follow-up. Regarding leader-supportive organizational climate and occupational well-being, expected differences between the profiles were not found. Overall, we propose that AI-MTL could be considered as a personal resource promoting the readiness to lead, at least, when deciding on whether to occupy leadership positions. Thus, AI-MTL should be regarded by HRM practitioners, especially, when readiness to lead is expected from candidates in the near future. In addition, to reinforce recognition and development of one’s motivation to lead, organizations are recommended to offer opportunities to accumulate leadership-related experience.